Motivations, Risks, Barriers, and Results Associated with the Adoption of Global Sourcing by Brazilian Companies: a Case-Based Study - Moema Pereira Nunes (BBR: Brazilian Business Review)
This article aims to identi fy the motivations behind g lobal s ourcing (GS) adoption , the associated risks and barriers , and the results that companies from emerging countries are achieving . The research explores the distinguishing features of these companies ' experience and examines established theories about GS that are based on companies from developed countries. In the article, a case - based study investigat ed four companies from the electrical and electronics industry in South Brazil. Data w ere collected through in - dep th interviews , documents , and direct observation. According to the research, t he main motivations for adopting GS are faster access to new technologies and establish ing a presence in global markets. It was also found that the opportunity to offer diversified products u sing the distribution channels already developed by companies motivate s GS adoption , a situation that prior literature has not identified . Despite the risks, t he absence of a broad local supply - base prompts companies to adopt GS. Further, the failure to fo rmalize barrier analysis processes creates difficulties f or companies . Th e main results associated with GS relate to innovation and reductions in the time taken to develop product s and reach market s . In this regard, c ompanies face a challenge to develop th e abilities required to compete for the advantages that t he global market can offer.